On estimation of maximal value of full diffusion time of infused and implanted dopants - E. L. Pankratov (International Journal of Mathematics for Industry)
In this paper, we estimate the maximal annealing time of dopant and/or radiation defects during the manufacturing of elements of integrated circuits by dopant diffusion and ion implantation. We introduce an analytical approach to estimate the maximal continuance of the diffusion process. We analyzed the influence of parameters of considered technological processes on the value of their maximal continuance of diffusion process.